Handbook of research on mobile marketing management - Pousttchi, Key, 1970-; Wiedemann, Dietmar G., 1977-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
"This book provides a compelling collection of innovative mobile marketing thoughts and practices"--Provided by publisher.
1. Mobile Marketing Management -- 2. Reviewing Mobile Marketing Research to Date -- 3. Framework for Mobile Marketing -- 4. Factors Affecting Mobile Advertising -- 5. Advertising Challenges in Ubiquitous Media Environments -- 6. Segmentation Challenges Posed by Transnationals in Mobile Marketing -- 7. Situation Approach as Success Factor of Mobile Marketing -- 8. A Framework for Understanding Mobile Value Offering through Multi-Country Studies -- 9. Supporting Marketing Practices -- 10. Mobile Customer Relationship Management (mCRM) -- 11. Employment and Acceptance of Near Field Communication in Mobile Marketing -- 12. Mobile Customer Acquisition in the Swiss Health Care Industry -- 13. Opportunistic Networks as an Enabling Technology for Mobile Word-of-Mouth Advertising -- 14. Theories behind Mobile Marketing Research -- 15. In Search of Successful Mobile Advertising -- 16. The Impact of Gender and Age on Consumer Responsiveness to Permission-Based Mobile Advertising -- 17. Mobile DM Coupon Promotion in Japan -- 18. Mobile Store Environment Dynamics -- 19. Mobile Loyalty Programs -- 20. Analyzing the Forwarding Behavior in Mobile Viral Marketing -- 21. Understanding Consumer Recommendation Behavior -- 22. Integrating Mobile Marketing into the Marketing Communication -- 23. Interactive Customer Retention Management for Mobile Commerce -- 24. Mobile Business and Mobile TV -- 25. Brand Driven Mobile Marketing.
Includes bibliographical references (p. 484-528) and index.
Also available in print.
Mode of access: World Wide Web.
Keywords: Telemarketing; Text messages (Telephone systems); Internet marketing; Internet advertising; Cell phones; Advertiser adoption; Business models in mobile marketing; Conceptualization of mobile marketing; Consumer and advertiser perception and attitudes; Cross-country comparison of consumer attitudes; Interactions among mobile devices, applications, and users; International mobile marketing regulation; Location based services; Mobile marketing campaign management; Mobile marketing campaign planning; Mobile marketing campaign types; Mobile marketing metrics; Mobile marketing practices; Mobile marketing research; Mobile marketing value system; Mobile technologies; Privacy issues and trust in mobile marketing; Standardization in mobile marketing; Success factors of mobile marketing; Theory building in mobile marketing; Electronic books